The ultimate Bonsai handbook the complete guide for beginners - Hirose, Yukio (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2020)
The ultimate bonsai handbook is a gardening guide and reference in one volume. It provides detailed information on all the basics of growing and caring for bonsai, such as: Understanding the different types; Tools, soils and containers; Transplanting, wiring, watering and pruning, and much more. The book's "learn through observation" approach fosters an in-depth and mindful exploration of this enduring art. Coverage of over 70 different types of bonsai and their requirements makes it an invaluable guide to different pines, maples, flowering and fruit bearing trees and other varieties--Source other than the Library of Congress.